Review on Tailoring PEDOT:PSS Layer for Improved Device Stability of Perovskite Solar Cells - Yijie Xia (MDPI AG, 2021)
Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) has high optical transparency in the visible light range and low-temperature processing condition, making it one of the most widely used polymer hole transport materials inverted perovskite solar cells (PSCs), because of its high optical transparency in the visible light range and low-temperature processing condition. However, the stability of PSCs based on pristine PEDOT:PSS is far from satisfactory, which is ascribed to the acidic and hygroscopic nature of PEDOT:PSS, and property differences between PEDOT:PSS and perovskite materials, such as conductivity, work function and surface morphology. This review summaries recent efficient strategies to improve the stability of PEDOT:PSS in PSCs and discusses the underlying mechanisms. This review is expected to provide helpful insights for further increasing the stability of PSCs based on commercial PEDOT:PSS.